PENGARUH METODE SIMULASI TERHADAP SIKAP REMAJA PUTRI TENTANG SADARI DI SMK NEGERI 1 SAMPIT 2019 - nana akbid kotim Maryana (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2020)
ABATRACT Background : Breast cancer is the second most common cancer in women in Indonesia. One of the early detection methods of breast cancer is breast self-examination. Most women do not do self-inpection due to their lack of knowledge of the Breast Self-Inspection. Research : The objective of this research is tu investigate Effect Of Simulation Methods On Adolescent Girls' Attitudes About Breast Self-Inspection At State Vocational High School 1 Of Sampit 2019. Research Method : The Pre Experimental Design with One Group Pretest - Posttest Design. This samples of the reaserch were taken by using the Stratified Random Sampling technique. The consisted of 63 respondents. The date of the research were analyzed by using Wilcoxon’s test and that of P for the variable of attitude is 0,000. Results : Meaning that there is an effect of the simulation method on the attitudes of female student in state vocational high school 1 of sampit . Conclusion : The following research es in the same field are recomended to compare between the practice methods and video methods with two groups, namely the Control Group and The Exsperimental Group.